An exploration of the associations among cognitive flexibility, attachment styles and life satisfaction. (28th October 2019) - Odacı, Hatice; Çıkrıkçı, Özkan; Çıkrıkçı, Neslihan; Aydın, Fatih
This research aimed to investigate the correlation between life satisfaction of university students in the young adult period with cognitive flexibility and attachment styles. The research group comprised 633 university students. The results of data analysis found a positive significant correlation between life satisfaction of students and cognitive flexibility ( r = .25, p < .01; 95% CI [0.17, 0.33]) and secure attachment style ( r = .17, p < .01; 95% CI [0.08, 0.25]), while there was a negative significant correlation between life satisfaction and the dismissive attachment style ( r = −.12, p < .01; 95% CI [−0.21, −0.04]). Among the results obtained in the study, the dependent variable of life satisfaction did not differ according to the sex ( t (628) = 1.49, p > .05) and grade variables ( F (5, 617) = 1.54, p > 0.05).